The spinal reflex cannot be perceptually separated from voluntary movements. (25th October 2013) - Ghosh, Arko; Haggard, Patrick
Key points: Voluntary motor commands and spinal reflexes both produce body movements that activate sensors located in the muscles, joints, tendon and skin. It is unknown whether perceptions generated by the sensory inputs from voluntary movements can be distinguished from perception of inputs due to spinal reflexes. Surprisingly, the perception of reflexes remains largely unaddressed. Knee‐jerk reflexes were perceived accurately on the basis of proprioceptive inputs alone, but perception was poorer when volunteers were instructed to voluntarily kick backwards or forwards as rapidly as possible in response to the tendon tap. This demonstrates that sensory inputs from a spinal reflex lead to movement perception. However, there is no clear perceptual landmark separating reflexes from voluntary movements, even when the two movements involve antagonistic muscles. These findings help us to understand how sensory feedback from body movement leads to movement perception and awareness of action. Abstract Both voluntary and involuntary movements activate sensors in the muscles, skin, tendon and joints. As limb movement can result from a mixture of spinal reflexes and voluntary motor commands, the cortical centres underlying conscious proprioception might either aggregate or separate the sensory inputs generated by voluntary movements from those generated by involuntary movements such as spinal reflexes. We addressed whether healthy volunteers could perceive the contribution of a spinal reflex during movements that combined both reflexive and voluntary contributions. Volunteers reported the reflexive contribution in leg movements that were partly driven by the knee‐jerk reflex induced by a patellar tendon tap and partly by voluntary motor control. In one condition, participants were instructed to kick back in response to a tendon tap. The results were compared to reflexes in a resting baseline condition without voluntary movement. In a further condition, participants were instructed to kick forwards after a tap. Volunteers reported the perceived reflex contribution by repositioning the leg to the perceived maximum displacement to which the reflex moved the leg after each tendon tap. In the resting baseline condition, the reflex was accurately perceived. We found a near‐unity slope of linear regressions of perceived on actual reflexive displacement. Both the slope value and the quality of regression fit in individual volunteers were significantly reduced when volunteers were instructed to generate voluntary backward kicks as soon as they detected the tap. In the kick forward condition, kinematic analysis showed continuity of reflex and voluntary movements, but the reflex contribution could be estimated from electromyography (EMG) recording on each trial. Again, participants' judgements of reflexes showed a poor relation to reflex EMG, in contrast to the baseline condition. In sum, we show that reflexes can be accurately perceived from afferent information. However, the presence of voluntary movement significantly impairs reflex perception. We suggest that perceptual separation between voluntary and reflex movement is poor at best. Our results imply that the brain has no clear marker for perceptually separating voluntary and involuntary movement. Attribution of body movement to voluntary or involuntary motor commands is surprisingly poor when both are present.